PENGARUH KONFLIK PERAN, KETIDAKJELASAN PERAN, KESAN KETIDAKPASTIAN LINGKUNGAN, LOCUS OF CONTROL DAN MOTIVASI KERJA TERHADAP KINERJA AUDITOR (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI PEKANBARU, PADANG DAN BATAM) - L, Al Azhar (Jurnal Ekonomi, 2013)
This study aimed to determine the effect of role conflict, role ambiguity, theimpression of environmental uncertainty, locus of control and motivation to workon the performance of auditors by public accountants in Pekanbaru, Padang andBatam.The used samples were 14 public accountants in Pekanbaru, Padang andBatam the total number of respondents 70 people. The method of data analysisused multiple regression using SPSS version 17.00.The results showed that roleconflict variables have on influence on the performance of the auditor with asignificance value of 0.011role ambiguity variable does not effect on theperformance oh the auditor with a significance value of 0.433, environmentaluncertainty variable does not affect on the performance of the auditor with asignificance value of 0.075, variable locus of control does not effect on theperformance of the auditor with a significance value of 0.515 and workmotivation variable does not effect on the performance of the auditor with asignificance value of 0689. Adjusted R square value is equal to 0323, or 32.3%,which means that the percentage effect of the independent variables in this studythe dependent variable is equal to 32.3%. While the remaining 67.7% is explainedby other variables, such as: the structure of the audit, experience and so forth.Kata Kunci : Role Conflict, Role Ambiguity, Uncertainty impressionEnvironment, Locus of Control, Work Motivation,Performance of Auditor.